Adipose tissue insulin resistance and lipidome alterations as the characterizing factors of non‐alcoholic steatohepatitis. (7th December 2021) - Guerra, Sara; Mocciaro, Gabriele; Gastaldelli, Amalia
Abstract: Background: The prevalence of non‐alcoholic fatty liver disease (NAFLD) is now 25% in the general population but increases to more than 55% in subjects with obesity and/or type 2 diabetes. Simple steatosis (NAFL) can develop into more severe forms, that is non‐alcoholic steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma leading to death. Methods: In this narrative review, we have discussed the current knowledge in the pathophysiology of fatty liver disease, including both metabolic and non‐metabolic factors, insulin resistance, mitochondrial function, as well as the markers of liver damage, giving attention to the alterations in lipid metabolism and production of lipotoxic lipids. Results: Insulin resistance, particularly in the adipose tissue, is the main driver of NAFLD due to the excess release of fatty acids. Lipidome analyses have shown that several lipids, including DAGs and ceramides, and especially if they contain saturated lipids, act as bioactive compounds, toxic to the cells. Lipids can also affect mitochondrial function. Not only lipids, but also amino acid metabolism is impaired in NAFL/NASH, and some amino acids, as branched‐chain and aromatic amino acids, glutamate, serine and glycine, have been linked to impaired metabolism, insulin resistance and severity of NAFLD and serine is a precursor of ceramides. Conclusions: The measurement of lipotoxic species and adipose tissue dysfunction can help to identify individuals at risk of progression to NASH.